Dysfunction of calcium-regulated exocytosis at a single-cell level causes catecholamine hypersecretion in patients with pheochromocytoma. (1st September 2022) - Houy, Sébastien; Streit, Laura; Drissa, Inès; Rame, Marion; Decraene, Charles; Moog, Sophie; Brunaud, Laurent; Lanoix, Joël; Chelbi, Rabie; Bihain, Florence; Lacomme, Stéphanie; Lomazzi, Sandra; et al.
Abstract: Neuroendocrine tumors constitute a heterogeneous group of tumors arising from hormone-secreting cells and are generally associated with a dysfunction of secretion. Pheochromocytoma (Pheo) is a neuroendocrine tumor that develops from chromaffin cells of the adrenal medulla, and is responsible for an excess of catecholamine secretion leading to severe clinical symptoms such as hypertension, elevated stroke risk and various cardiovascular complications. Surprisingly, while the hypersecretory activity of Pheo is well known to pathologists and clinicians, it has never been carefully explored at the cellular and molecular levels. In the present study, we have combined catecholamine secretion measurement by carbon fiber amperometry on human tumor cells directly cultured from freshly resected Pheos, with the analysis by mass spectrometry of the exocytotic proteins differentially expressed between the tumor and the matched adjacent non-tumor tissue. In most patients, catecholamine secretion recordings from single Pheo cells revealed a higher number of exocytic events per cell associated with faster kinetic parameters. Accordingly, we unravel significant tumor-associated modifications in the expression of key proteins involved in different steps of the calcium-regulated exocytic pathway. Altogether, our findings indicate that dysfunction of the calcium-regulated exocytosis at the level of individual Pheo cell is a cause of the tumor-associated hypersecretion of catecholamines. Highlights: Mechanisms controlling catecholamine secretion are deregulated in human pheochromocytoma tumor single cell. In human pheochromocytoma cells, exocytic events increase and occur with a faster kinetic leading to hypersecretion. Key players of the secretory pathway are upregulated in human pheochromocytoma tissue.